2003
DOI: 10.1111/j.1553-2712.2003.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Emergency Department Population and Their Interest in Preventive Health Education

Abstract: Of the 878 subjects in the study group, 96% were interested in obtaining information about one or more preventive health issues. An opportunity exists to respond to this interest by providing material for public health education in the waiting area of EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 17 publications
4
22
0
1
Order By: Relevance
“…In this setting, we found that the large majority (97%) of women were interested in receiving a sample of EC when one was offered. This supports prior work, which found that 96% of people waiting to be seen by an academic emergency department were interested in receiving information about one or more preventive health issues, 25 but is in contrast to a study that recruited women from 3 primary care clinics in North Carolina, which reported that 49% of women declined an advance prescription for EC. 26 The reason women in our study were more interested in advance EC may reflect differences inherent in the populations studied; alternatively, the counseling about EC that was provided before offering EC may have impacted women's level of interest, or women may have simply felt that a free medication sample had more value than a prescription.…”
Section: Discussionsupporting
confidence: 83%
“…In this setting, we found that the large majority (97%) of women were interested in receiving a sample of EC when one was offered. This supports prior work, which found that 96% of people waiting to be seen by an academic emergency department were interested in receiving information about one or more preventive health issues, 25 but is in contrast to a study that recruited women from 3 primary care clinics in North Carolina, which reported that 49% of women declined an advance prescription for EC. 26 The reason women in our study were more interested in advance EC may reflect differences inherent in the populations studied; alternatively, the counseling about EC that was provided before offering EC may have impacted women's level of interest, or women may have simply felt that a free medication sample had more value than a prescription.…”
Section: Discussionsupporting
confidence: 83%
“…Due to ED overcrowding, many patients have prolonged waiting periods, are willing to use this time to receive immunizations, and accept vaccinations in the ED when offered. [8][9][10] The purpose of this study was to evaluate a program to provide influenza (flu) and pneumococcal vaccines to high-risk patients in the ED. The primary hypothesis was that patients would be amenable to an ED-based program that provided appropriate immunizations when they were at high risk for these diseases.…”
mentioning
confidence: 99%
“…Seniors were expected to use such services even more often and to display preventive behaviours. 30 Males seemed to fulfil this expectation, but females did not. Only middle aged and highly educated females (cluster 6) participated in gynaecological preventive testing.…”
Section: Social Inequality and Healthmentioning
confidence: 93%